Google Earth Engine: Mapeamento das Mudanças na Cordilheira Vilcanota-Peru - Villavicencio, Lourdes Milagros Mendoza (2018)
The exercise of mapping through medium or high resolution satellite images to a large extent is a computationally expensive procedure. It may take days or weeks to get the final maps. To increase the speed of time-consuming procedures, the use of supercomputers is a common practice. GoogleTM has developed a product designed specifically for Earth (Earth Engine) purposes, allowing users to leverage their computing power and the mobility of a cloudbased solution. In this work, we explore the feasibility of using this platform for the mapping of the soil cover and the dynamics through time, making use of satellite images, as an application was made the mapping of the Vilcanota mountain range in Southeastern Peru, with the objective of analyzing the changes in ice cover between the years 1985, 1996, 2006 and 2016. The results pointed to the evidence of the regression in the ice cover of the mountain range, showing that the region below 5300 meters of altitude contributed with the greater loss of ice cover , while the region with higher altitudes presented stability or slight increase in ice cover. The methodology can be easily applied to other glaciers in the world and develop analysis of time spaces on a global scale